Historische Forschung in der Religionsdidaktik - Schröder, Bernd (Theo-Web, 2020)
There is no doubt that there is historical research in religious education studies and also in religious didactics. All relevant studies have a design that can be identified as "historical" on the basis of the underlying question, the epistemological interest, the subject, the methods and theories of reference. The article offers, in addition to scientific theoretical considerations, a material overview of historical research in the field of religious didactics. But it concludes that it would be misleading at present to speak of an established format of historical-religious-didactic research.